Risks of Sociotechnical Convergence in Digital Era - Vitaly ZOTOV; Irina ASEEVA; Vladimir BUDANOV; Viktoria BELKINA (Communications of International Proceedings, 2021)
The process of intromission of modern digital technologies into all spheres of social and human life which in this article is called sociotechnical convergence is happening rapidly and in a risky way. The development of new technologies has a significant influence on the transformation of modern society, often bringing about risks unknown before and making managing more complicated. In this article we offer a classification and analyses of risks and side effects of digitalization.
Keywords: philosophy of science and technology; network sociology; digital technology; risks; sociotechnical convergence